A Study of the Fishery Logistics System in Fisheries Management Area (WPP) 715, Tomini Bay, Central Sulawesi - Fachrudin Fachrudin; Umar Umar; Mawar Mawar; Moh.Arif Latjuba (Jurnal Penelitian Pendidikan IPA, 2025)
The Fish Logistics System (SLI) plays a crucial role in the efficient management of fisheries supply chains, covering all activities from procurement to distribution. This study aims to: estimate local fish consumption needs in Parigi Moutong, Poso, and Tojo Unauna Regencies; and analyze the traceability and logistics system, including production capacity (catch and cultivation) and distribution flows from fishermen to end consumers. Using a descriptive research design with qualitative and quantitative approaches, data were collected through surveys, in-depth interviews, and observations. The results show that Parigi Moutong and Tojo Unauna Regencies have a significant fish production surplus (Approximately 70.9 million kg) in 2024, while Poso Regency faces a deficit (of -7.8 million kg). The distribution flow includes local, regional, and national markets, with significant exports to Malaysia, Singapore, and Colombia. The study highlights the need to strengthen infrastructure and integrate supply chain management to optimize the fisheries potential of WPP 715, ensure food security, and boost regional economies.